2019
DOI: 10.1002/jcb.28819
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 promotes proliferation, migration, and invasion of glioblastoma through transcriptional upregulation of lncRNA HOXC‐AS3

Abstract: HOXB13 exerts a close relation in several human cancers. This study explored the role of HOXB13 in glioblastoma (GBM), a brain tissue with the highest aggressive rate and mortality in adults. Through microarray and immunohistochemistry analyses, HOXB13 was highly expressed in GBM tissues. Furthermore, we showed that high‐level expression of HOXB13 in GBM was associated with worse survival, suggesting that HOXB13 could be a prognostic marker for patients with GBM. GBM cells U87 and U251 overexpressing HOXB13 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…HOXC-AS3 is a long coding RNA (lcRNA) with currently no known data in skeletal muscle, with some literature in cancer and mesenchymal stem cell (MSC) fields 76 . Indeed, MSC’s administered with silencing HOXC-AS3 prevented bone loss by enhancing HOXC10 expression 77 , and HOXC-AS3 upregulation has also been linked with aggressive cancer 78 . Interestingly, we were able to identify that together with associated hypomethylation, in a region close to the lcRNA HOXC-AS3, there was significantly increased gene expression of HOXC-AS3 (and an average, yet not significant increase in HOXC10 gene expression) in aged muscle cells at 7 days of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…HOXC-AS3 is a long coding RNA (lcRNA) with currently no known data in skeletal muscle, with some literature in cancer and mesenchymal stem cell (MSC) fields 76 . Indeed, MSC’s administered with silencing HOXC-AS3 prevented bone loss by enhancing HOXC10 expression 77 , and HOXC-AS3 upregulation has also been linked with aggressive cancer 78 . Interestingly, we were able to identify that together with associated hypomethylation, in a region close to the lcRNA HOXC-AS3, there was significantly increased gene expression of HOXC-AS3 (and an average, yet not significant increase in HOXC10 gene expression) in aged muscle cells at 7 days of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Several studies have shown that HOXB13 plays a crucial role in several types of cancers. 13 Men with the G84E mutation in HOXB13 have an increased risk of prostate cancer. 14 Low HOXB13 expression is a poor prognostic factor in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that HOXB13 is involved in the progression of cancer, including prostate, breast cancers, and glioblastoma [9,13,29]. The expression levels and nuclear localization of HOXB13 have also been suggested to be predictive markers for bladder cancer [30,31]; however, the physiological function of HOXB13 in the brain remains completely unknown.…”
Section: Discussionmentioning
confidence: 99%